Perancangan dan Implementasi Sistem Informasi Launchpad Cryptocurrency pada PT. Pintar Media Teknologi - Suwarno, Suwarno; Valentino, Elvin (Computer Based Information System Journal, 2024)
Blockchain technology has become a major focus in the development of decentralized web applications, opening a new era in the evolution of the internet known as Web3. In the midst of this development, startup company PT. Pintar Media Teknologi introduced a cryptocurrency launchpad application that relies on blockchain technology to provide decentralized solutions in crypto asset trading. The author has the opportunity to conduct research at PT. Pintar Media Teknologi to build a cryptocurrency launchpad application. The blockchain application development methodology applied is the Agile Scrum methodology. Through analyzing the features developed, such as Entity Relationship Diagram design, database design, to the implementation of key features such as authentication using Web3, token management, and launchpad management. The results of this study provide insight into the practice of developing blockchain applications and the author's contribution to this research is to design and implement a cryptocurrency launchpad information system according to the needs of stakeholders so as to accelerate the product development process.